Cross-Linking with Polyethylenimine Confers Better Functional Characteristics to an Immobilized β-glucosidase from Exiguobacterium antarcticum B7 - Rodrigues de Melo, Ricardo; Alnoch, Robson Carlos; Silva de Sousa, Amanda; Harumi Sato, Hélia; Ruller, Roberto; Mateo González, César (Catalysts, 2019)
β-glucosidases are ubiquitous, well-characterized and biologically important enzymes with considerable uses in industrial sectors. Here, a tetrameric β-glucosidase from Exiguobacterium antarcticum B7 (EaBglA) was immobilized on different activated agarose supports followed by post-immobilization with poly-functional macromolecules. The best result was obtained by the immobilization of EaBglA on metal glutaraldehyde-activated agarose support following cross-linking with polyethylenimine. Interestingly, the immobilized EaBglA was 46-fold more stable than its free form and showed optimum pH in the acidic region, with high catalytic activity in the pH range from 3 to 9, while the free EaBglA showed catalytic activity in a narrow pH range (>80% at pH 6.0–8.0) and optimum pH at 7.0. EaBglA had the optimum temperature changed from 30 ◦C to 50 ◦C with the immobilization step. The immobilized EaBglA showed an expressive adaptation to pH and it was tolerant to ethanol and glucose, indicating suitable properties involving the saccharification process. Even after 9 cycles of reuse, the immobilized β-glucosidase retained about 100% of its initial activity, demonstrating great operational stability. Hence, the current study describes an efficient strategy to increase the functional characteristics of a tetrameric β-glucosidase for future use in the bioethanol production. We acknowledge support by the CSIC Open Access Publication Initiative through its Unit of Information Resources for Research (URICI) Peer reviewed